PENERAPAN METODE CROSSDOCKING UNTUK MEMINIMUMKAN BIAYA DISTRIBUSI DAN PERSEDIAAN PADA PT. XYZ - St. Nova Meirizha; Ari Andriyas Puji; Ardi Adrian (Jurnal Surya Teknika, 2020)
Rapid technological development changes the form of competition between profit-oriented companies. The presence of new methods of company management is getting more intense due to the demands of a competitive advantage with other companies. One of the areas that can create competitive advantage is the operational sector. Furthermore, Supply Chain Management has become one of the main components as a competitive strategy to develop the productivity and profitability capabilities of a company. Meanwhile, crossdocking systems have been found for a long time, but the application is often not too significant for companies and there is still room for optimization. Therefore, the researcher was interested in carrying out research related to crossdocking. In this study, the target company is PT. XYZ as a distribution center company that has problems in managing distribution costs and supplies to its partners. By implementing crossdocking, it can help companies in minimizing distribution and inventory costs. The steps in this study are determining vehicle distribution routes, calculating the number of distribution fleets, scheduling distribution fleets, calculating the total safety stock and calculating the ratio of the total cost of supplies in the current condition to the proposed conditions. The research results obtained 2 optimal distribution routes with a total distribution fleet of 2 units, divided into fleet 1 with a capacity of 800 units and fleet 2 with a capacity of 767 units. As for the scheduling results, the makespan value of each fleet is obtained, namely 240 minutes for fleet 1 and 248 minutes for fleet 2. The amount of safety stock for each type of cellphone is Y19 with 27 units of safety stock, Y12 with 102 units of safety stock, Y30 with safety stock 75 units and V19 with safety stock 54 units. The total cost of supplies is 2,989,055 rupiah in one order process.